Accountability Perspective: Implementation and Reporting on Spending Fund of Papua Special Autonomy - Agustinus, John (Information Management and Business Review, 2015)
The purposes of this research to identify (1) the Special Autonomy Law, local government regulations and compliance in determining financial performance or management of special autonomy funds, (2) compliance, supervision, accountability of special autonomy funds in determining accountability for the management of special autonomy funds, (3) knowledge related to education and experience on which to base effective management and efficient fund and provide benefits to the people of the province. The qualitative paradigm is used in this research and phenomenology methods. The findings showed: Implementation of accountability required a strong commitment from the governor and the entire staff of the agency concerned, ensure proper use of resources is consistent with legislation in force, indicating the level of achievement of goals and objectives that have been set. Oriented to achieving the vision and mission, as well as the results and benefits obtained, honest, objective, transparent, and accurate, Presenting success or failure in achieving the goals and objectives that have been set.